Collaborative Governance dalam Upaya Pencegahan Pernikahan Anak Usia Dini di Kabupaten Ogan Komering Ulu - Hefsa Pebriani; Annada Nasyaya (Jurnal Pemerintahan dan Politik, 2023)
This research was conducted to find out Collaborative Governance in efforts to prevent early marriage in Ogan Komering Ulu Regency. The increase in early marriage in Ogan Komering Ulu district has made the government collaborate in overcoming this problem. In this research, the research method used is descriptive-qualitative with data collection techniques such as interviews, observation and documentation.In this study, Miles and Huberman latest analysis method was use with Atlas.ti software. This research uses Ansell and Gash's (2008) Collaborative Governance theory with four variables, namely initial conditions, facilitative leadership, institutional design, and collaboration process. The results of this study show that Collaborative Governance in efforts to prevent early marriage in Ogan Komering Ulu District is still not running optimally. This is because face-to-face dialog and leadership roles are still not optimal. Although, this collaboration is able to reduce the number of early marriages in Ogan Komering Ulu Regency. Based on the results of the data analysis conducted, the suggestion that the author can give is to increase socialization or counseling to the wider community by utilizing current technology such as social media regarding the impact of early marriage and sex education and making agenda settings so that face-to-face dialogue continues to run optimally.